Step right up : how Doc and Jim Key taught the world about kindness - Bowman, Donna Janell; Minter, Daniel (New York : Lee & Low Books Inc., 2016)
A picture book biography of Dr. William Key, a former slave and self-trained veterinarian who taught his horse, Jim, to read and write and who together with Jim became one of the most famous traveling performance acts around the turn of the twentieth century.
School Library Journal, October 2016
Booklist starred, September 2016
Pub Weekly, August 2016
Kirkus Starred, August 2016
Horn Book, April 2017
Bulletin (Center for Children's books), December 2016
Keywords: Key, Bill, -- 1833-1909 -- Juvenile literature; Beautiful Jim Key (Horse) -- Juvenile literature; Key, Bill, -- 1833-1909.; Horse trainers; Beautiful Jim Key (Horse); Moral education -- History; Horses -- Training -- History; Human-animal communication; Human-animal relationships; Key, Bill, -- 1833-1909.; Horse trainers -- Biography; Beautiful Jim Key (Horse); Animal communication; Human-animal relationship; Biographies